The Effect of Oral Misoprostol in Prelabour Rupture of Membranes at Term - NAEEMA KAUSAR, RAKHSHANDA REHMAN, ASIA PARVEEN, KANEEZ FATIMA, (Journal of Fatima Jinnah Medical University, 2018)
OBJECTIVE: The effect of oral Misoprostol for induction of labour in Primigravidas with prelabour rupture of membranes at term. STUDY DESIGN: This is Quasi-experimental study. PLACE AND DURATION OF STUDY: This study was conducted at the Department of Obstetrics and Gynecology Unit-II Fatima Jinnah Medical College/ Sir Ganga Ram Hospital, Lahore, during the period of one year (1-1-2008 to 31-12-2008). SUBJECTS AND METHODS: This study included sixty singleton primigravidas with cephalic presentation who had prelabour rupture of membranes (PROM) at term with no contraindication for induction of labour or for Misoprostol usage.100 microgram (µg) of Misoprostol was given orally at 4 hours interval for the maximum of two doses with or without Oxytocin augmentation. The outcome measures included induction to delivery time, oxytocin augmentation, mode of delivery, fetal outcome and maternal complications. RESULTS: Majority of subjects (58.34%) required two doses of Misoprostol. In these women, the induction to delivery time was longer (9.6 hrs) as compared to subjects who had single dose (8.2 hrs).about mode of delivery, 50 women (83.30%) delivered vaginally with episiotomy, 9 (25%) had emergency lower segment Caesarean section (LSCS) due to fetal distress and 1 (1.6%) had instrumental delivery. About 80% of women who had vaginal delivery also required augmentation with Oxytocin. The maternal complications were nausea/vomiting in 4 (6.6%) and fever in 2 patients (3.3%). All newborns had good Apgar score at 1 & 5 minutes. CONCLUSION: Oral Misoprostol is a safe and effective agent for induction of labour in primigravidas with PROM at term in a set up with adequate feto-maternal monitoring facilities.